2013
DOI: 10.4236/ojs.2013.35039
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Chemometric Data

Abstract: The objective of this paper is to present a review of different calibration and classification methods for functional data in the context of chemometric applications. In chemometric, it is usual to measure certain parameters in terms of a set of spectrometric curves that are observed in a finite set of points (functional data). Although the predictor variable is clearly functional, this problem is usually solved by using multivariate calibration techniques that consider it as a finite set of variables associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…A different approach to tackling the problem of water content estimation from reflectance is based on considering spectral signatures as continuous curves instead of discrete values. A review of potential applications of this kind of functional data analysis to chemometrics is provided by Aguilera, Escabias, Mariano, Valderrama, and Aguilera-Morillo (2013) and by Saeys, Keteleare, and Darius (2008). In exemplifying the use of functional models, Saeys et al (2008) concluded that functional data analysis is comparable to partial least squares regression (PLSR) in terms of predictive ability.…”
Section: Introductionmentioning
confidence: 99%
“…A different approach to tackling the problem of water content estimation from reflectance is based on considering spectral signatures as continuous curves instead of discrete values. A review of potential applications of this kind of functional data analysis to chemometrics is provided by Aguilera, Escabias, Mariano, Valderrama, and Aguilera-Morillo (2013) and by Saeys, Keteleare, and Darius (2008). In exemplifying the use of functional models, Saeys et al (2008) concluded that functional data analysis is comparable to partial least squares regression (PLSR) in terms of predictive ability.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral data are the absorbance spectrum of chemicals and can be seen as a function of the wavelength; thus, it is natural to work with functional data in chemometrics. Consult Saeys et al 12 and Aguilera et al 13 for many applications of functional data analysis in chemometrics. Since, Cardot et al 14 the scalar‐on‐function regression model, whose response variable is scalar and predictors consist of random curves, has been well studied in chemometrics analysis of spectral data, see, for example, previous works 15–23 .…”
Section: Introductionmentioning
confidence: 99%
“…Spectral data are the absorbance spectrum of chemicals and can be seen as a function of the wavelength; thus, it is natural to work with functional data in chemometrics. Consult Saeys et al (2008) and Aguilera et al (2013) for many applications of functional data analysis in chemometrics. Since Cardot et al (1999), the scalar-on-function regression model, whose response variable is scalar and predictors consist of random curves, has been well studied in chemometrics analysis of spectral data (see e.g., Ferraty and Vieu, 2002;Reiss and Odgen, 2007;Matsui et al, 2008;Jiang and Martin, 2008;Kramer et al, 2008;Aguilera et al, 2010Aguilera et al, , 2016Montesinos-Lopez et al, 2017;Smaga and Matsui, 2018).…”
Section: Introductionmentioning
confidence: 99%